PENGARUH MODEL CONTEXTUAL TEACHING AND LEARNING BERBASIS APLIKASI NEARPOD DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM TERHADAP MINAT BELAJAR SISWA DI MAN 2 MAJALENGKA - Fatma, Syifa Nurul; Syamsul, Encu Mulya; Burhani, Ahmad Zacky (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of the Contextual Teaching and Learning (CTL) model based on the Nearpod application on students’ learning interest in Islamic Religious Education (PAI) at MAN 2 Majalengka. The method used is quantitative with a quasi-experimental design in the form of a Nonequivalent Pretest-Posttest Control Group Design. The sample consisted of two tenth-grade classes, each with 35 students. The data collection instrument was a learning interest questionnaire that had been tested for validity and reliability. The results showed a significant increase in learning interest in the experimental group after being taught using the CTL model supported by Nearpod. The t-test results indicated a significance value of 0.000 (p < 0.05), meaning there was a statistically significant difference between the experimental and control groups. The increase was observed in four aspects of learning interest: attention, engagement, interest, and enjoyment. This study concludes that the implementation of the CTL model using Nearpod is effective in enhancing students’ interest in learning PAI and can serve as an alternative interactive and contextual technology-based learning strategy.